Prevalence of goitre among school going children in urban area of Dehradun - Sharma, Utkarsh; Sharma, Janmejai Prasad; Sharma, Arti; Kumar, Alok; Shukla, Navin (International Journal of Research in Medical Sciences, 2017)
Background:Iodine is an important micro-nutrient required for human nutrition. Iodine Deficiency Disorders (IDDs) are one of the major world-wide public health problems of today which causes wide spectrum of disabilities. It includes impairment of reproductive functions, lowering of IQ levels in school age children, goiter, deaf mutism, mental defects, weakness and paralysis of muscles as well as lesser degree of physical dysfunction. Methods:Selection of population: The school children in age group of 6-18 years from both the sexes were screened from SGRR Schools of different locations at Dehradun, after taking approval from principal and the parents. Results:The prevalence of goitre among school going children was 5%. Prevalence of goitre among female was 6.4% compare to male were 4.1%. There was significant association found between prevalence of goitre and vegetarian diet. In pre pubertal age (11-14 years) maximum (7.6%) cases of goitre were seen. A significant association of goitre with pallor was also observed Conclusion:The sustained efforts in implementing the guidelines of National Iodine Deficiency Disorders Control Programme (NIDDCP) have been able to reduce the prevalence of goitre in Uttrakhand state. In spite of reduction in prevalence over years, goitre continues to be a major public health problem in the state.